53 A REVIEW OF THE RAPID ACCESS FRAILTY TEAM (RAFT) IN THE EMERGENCY DEPARTMENT OF A MODEL THREE HOSPITAL. (25th October 2022) - O'Neill, A; Brady, A; Donnelly, T; McGlynn, J; Moore, A; Hopper, C
Abstract: Background: The Rapid Access Frailty Team (RAFT) in the Emergency Department (ED) has evolved since 2016. The team comprises of 1 senior occupational therapist and 1 senior physiotherapist. The focus of the team is recognition and management of frailty in ED. Patients discharged by RAFT in ED are often followed up in our Rapid Access Frailty Hub. This audit examined the incidence and outcomes of frail older persons presenting to our ED and the impact of intervention from the Rapid Access Frailty team. Methods: A Variable Indicative of Placement Risk (VIP) positive patient triggers an assessment by RAFTT in ED post triage. Analysis of intervention and discharge destination were used to assess the effectiveness and role of the team. Results: We compared data over two distinct 6 month periods, between September – February 2019-2020 and 2021-2022. 2723 patients >75 presented to ED in 2019 - 2020. Of these, 1620 were VIP positive patients. 628/1620 patients were seen by RAFFT. 443/628 (70.5%) assessed by RAFT were discharged. In comparison to 2021-2022, we saw an increase with 2818 patients >75, 1657 of which were triaged as frail. 559 patients were assessed by RAFTT and 286/559 (51%) were discharged. We observed 20% reduction in our discharge rate. Most patients received on average five interventions each. 60% of patients received a mobility assessment, 45% received falls prevention intervention and 37% were provided with equipment to facilitate discharge. Conclusion: Over a two year period we observed an increase in frail patients presenting to our ED. Comprehensive assessment by RAFT in ED is promoting discharge. The follow up through the frailty hub has enhanced our ability to follow up in a timely manner. We hypothesize that the reduction in discharge rates in 2021- 2022 may be due to deconditioning experienced by older adults post pandemic and the increased demand for medical intervention and admission.